Comparison of two in situ reference methods to estimate indigestible NDF by near infrared reflectance spectroscopy in alfalfa. Issue 6 (June 2021) - Zhang, G.J.; Wang, Y.; Yan, Y.H.; Hall, M.H.; Undersander, D.J.; Combs, D.K.
Abstract: Undigested forage neutral detergent fiber (uNDF) from long-term ruminal in situ incubations are used to estimate indigestible neutral detergent fiber (iNDF). Measurement of iNDF is important in forage evaluation because it defines the potentially digestible pool of neutral detergent fiber (NDF). Near-infrared reflectance spectroscopy (NIRS) can be calibrated to in situ reference sets to rapidly predict uNDF. Our objective was to compare uNDF estimates after 240 h of incubation when two types of bags were used in the in situ reference method. The bags compared were 4 cm × 5 cm Ankom F57 bags (25 micron pore size), and 5 cm × 10 cm Ankom in situ bags (50 micron pore size). Alfalfa samples from Pennsylvania and Wisconsin ( n = 144) of different varieties and harvest intervals were used. One-half or two gram samples, respectively, were weighed into the small and large bags in triplicate. Mass to surface area was 0.05 and 0.02 g/cm 2 for the small and large bags, respectively. The iNDF content after 240 h incubation was evaluated by two types bags in three rumen-cannulated Holstein cows. Each dried and ground forage was also scanned to determine the visible–near-infrared-reflectance spectra with a FOSS 6500 spectrophotometer. Prediction equations were developed for each bag type using modified partial least square regressions. The estimated iNDF fraction from small and large bags were 13.75% and 9.97%, respectively (SED = 0.39, P < 0.001). The coefficient of determination for calibration (R 2 ), cross-validation (1 - VR), calibration standard deviation (SEC), and interactive authentication standard deviation (SECV) was 0.94, 0.92, 0.85 and 0.98 for values determined with the small bag and 0.88, 0.85, 1.12 and 1.27 for iNDF for values determined with the large bag, respectively. Results indicate that iNDF varies among alfalfa cultivars and NIRS can be used to quickly and quantitatively estimate iNDF content in alfalfa. Bag type influences 240h NDF residues. NIRS predictions of iNDF from the small bag calibration set had higher R 2 and lower SEC and SECV than the large bag calibrations. Abstract : Near infrared reflectance spectroscopy; Indigestible neutral detergent fiber; Bag types; Alfalfa